NO and SO2 emissions in palm kernel shell catalytic steam gasification with in-situ CO2 adsorption for hydrogen production in a pilot-scale fluidized bed gasification system - Khan, Z. (Elsevier Ltd, 2019)
The NO and SO2 emissions in enhanced hydrogen production from palm kernel shell (PKS) steam gasification with integrated catalytic adsorption steam gasification is investigated. The influence of steam and adsorbent to biomass ratios (1.5â2.5, 1.0â1.5), temperature (600â750 Â°C), biomass particle size (0.355â2.0 mm) and fluidization velocity (0.15â26 m/s) was reported. The results inferred that lower temperature (600 Â°C) contributed to emissions of NO (30 ppm) and SO2 (110 ppm) whereas high steam to biomass ratio (2.5 wt/wt) produced emissions of <30 ppm and <110 ppm, respectively, at experimental conditions of 675 Â°C, adsorbent to biomass ratio of 1.0 (wt/wt) and catalyst to biomass ratio of 0.1 (wt/wt). The lowest average minimum NO and SO2 concentration of 16 ppm and 46 ppm, respectively, was observed at 675 Â°C, steam to biomass ratio of 2.0 (wt/wt), adsorbent to biomass ratio of 1.5 (wt/wt) and catalyst to biomass ratio of 0.1(wt/wt). Nevertheless, emissions were prorportional to fluidization velocities and small particle size (0.3â0.5 mm) contributed to high NO and SO2. The comparative studies found that the present study produced similar emission of NO (30 ppm) when compared with commercial indirect heated fluidized bed gasifier using steam as an oxidizing agent. Besides, some other studies operated at high temperature reported high NO and SO2 concentration which might be due to the temperature being the most influential variable in the context. Â© 2019 Elsevier Ltd